Inflammation-Induced Alternative Pre-mRNA Splicing in Mouse Alveolar Macrophages - Janssen, William J. (G3 (Bethesda), 2019)
Alveolar macrophages serve as central orchestrators of inflammatory responses in the lungs, both initiating their onset and promoting their resolution. However, the mechanisms that program macrophages for these dynamic responses are not fully understood. Over 95% of all mammalian genes undergo alternative pre-mRNA splicing. While alternative splicing has been shown to regulate inflammatory responses in macrophages in vitro, it has not been investigated on a genome-wide scale in vivo. Here we used RNAseq to investigate alternative pre-mRNA splicing in alveolar macrophages isolated from lipopolysaccharide (LPS)-treated mice during the peak of inflammation and during its resolution. We found that lung inflammation induced substantial alternative pre-mRNA splicing in alveolar macrophages. The number of changes in isoform usage was greatest at the peak of inflammation and involved multiple classes of alternative pre-mRNA splicing events. Comparative pathway analysis of inflammation-induced changes in alternative pre-mRNA splicing and differential gene expression revealed overlap of pathways enriched for immune responses such as chemokine signaling and cellular metabolism. Moreover, alternative pre-mRNA splicing of genes in metabolic pathways differed in tissue resident vs. recruited (blood monocyte-derived) alveolar macrophages and corresponded to changes in core metabolism, including a switch to Warburg-like metabolism in recruited macrophages with increased glycolysis and decreased flux through the tricarboxylic acid cycle.